2020
DOI: 10.3390/nano10040739
|View full text |Cite
|
Sign up to set email alerts
|

Soil Application of Nano Silica on Maize Yield and Its Insecticidal Activity Against Some Stored Insects After the Post-Harvest

Abstract: Maize is considered one of the most imperative cereal crops worldwide. In this work, high throughput silica nanoparticles (SiO2-NPs) were prepared via the sol–gel technique. SiO2-NPs were attained in a powder form followed by full analysis using the advanced tools (UV-vis, HR-TEM, SEM, XRD and zeta potential). To this end, SiO2-NPs were applied as both nanofertilizer and pesticide against four common pests that infect the stored maize and cause severe damage to crops. As for nanofertilizers, the response of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…One of the advantages for using starch as a stabilizing agent, aside from its potential power to convert the ions of silver to zero-valent silver, is the presence of huge hydroxy groups that stabilize the formed nanoparticles in nanoform. In our published work 7 , 28 , 43 47 , the prepared nanoparticles were extensively characterized using advanced tools. Secondly, as mentioned in the experiment part for the preparation of SiO 2 NPs, condensation reaction was performed for this synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages for using starch as a stabilizing agent, aside from its potential power to convert the ions of silver to zero-valent silver, is the presence of huge hydroxy groups that stabilize the formed nanoparticles in nanoform. In our published work 7 , 28 , 43 47 , the prepared nanoparticles were extensively characterized using advanced tools. Secondly, as mentioned in the experiment part for the preparation of SiO 2 NPs, condensation reaction was performed for this synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It was well documented that colloidal silver nanoparticles are small enough to penetrate into the cell and subsequently into the nucleus and to directly interact with the nuclear DNA resulting in the modulation of gene expression profiles 21 24 , particularly genes related to inflammatory response (e.g., IL1β and TNF-α) 25 . Moreover, several studies stated that the concentration of Ag in broiler muscles could increase when the dose level of AgNPs is increased 26 – 28 ; these nanoparticles may interact with proteins, resulting in biological and physiological changes in the cells 29 . Nabinejad et al 30 stated that the muscles and organs of the poultry may transfer the AgNPs to the consumers, leading to adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Si treatment can alleviate drought stress, salt stress, heat stress, and oxidative damage. The beneficial role of Si in drought conditions is mainly due to enhanced water retention aiding photosynthesis [21][22][23][24][25] . Potassium silicate (K-silicate) is a source of highly soluble K and Si.…”
mentioning
confidence: 99%
“…It has recently been observed that SiO 2 nanoparticles (NPs) provide additional protection to plant cells subject to As stress, mediating a strengthening of plant cell walls by increasing their thickness and altering their composition [106]. Likewise, in maize, field applications of SiO 2 -NPs resulted in a large improvement to growth, but interestingly, there were disruptive effects as well with the Si found to induce a pesticide response for the crop during storage [107]. Similarly, some soil invertebrates demonstrate avoidance behaviors to SiO 2 NP Santos et al [108], and it has been shown that they can increase soil bacteria community diversity [109].…”
Section: Limitations and Considerations For Fmsn Use In Soilsmentioning
confidence: 99%